Design of warm dielectric terminations and electrical breaks for high-temperature superconducting power cables. Issue 1 (1st May 2022) - Mensah, P; Lopez, H; Cheetham, P; Kim, C H; Pamidi, S
Abstract: Large electric transportation systems such as electric aircraft and electric ships have been designed with multiple high temperature superconducting (HTS) power cables as part of superconducting power distribution network, and a good electric insulation for the power cables is a critical design requirement needed to be considered. This is because terminations in HTS cable represent a location of significant electrical and thermal stresses and needs to be addressed to reduce the substantial heat load that might be introduced into the cryogenic system. The use of a warm dielectric termination is seen as a potential solution to reduce the electrical standoffs required as part of the design and allow for a high-power dense termination design. A warm dielectric termination design using commercially off-the-shelf ceramic breaks as electrical breaks is explored and withstand and partial discharge measurements are performed to determine the viability of the design concept.